DARI ANALISIS FOURIER KE ANALISIS WAVELET (From Fourier Analysis to Wavelet Analysis) - Priatna, Bambang Avip (Jurnal Pengajaran MIPA, 2001)
In this article we will compare the classical methods of Fourier analysis with the never methods of wavelet analysis. Fourier methods are not always a good tool to recapture the signal, particularly if it is highly non-smooth because too much Fourier information is needed to reconstruct the signal locally. In this case, wavelet analysis is often very effective because it provides a simple approach for dealing with local aspects of a signal.